Implementasi Penyaluran Kartu Huma Betang Sejahtera dan Respon Masyarakat di Kecamatan Pasak Talawang - Inyi Inyi; Emi Anggraini; Ade Yuniati; Verra Rizki Amelia (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to describe the implementation of the distribution of the Huma Betang Sejahtera Card (KHBS) and the community response in Pasak Talawang District, Kapuas Regency. The KHBS program is a policy of the Central Kalimantan Provincial Government to improve community welfare through cash assistance, food assistance, and health and education services for beneficiaries. The activity was carried out through mentoring and socialization with data collection techniques in the form of observation and documentation. The activity stages include preparation, implementation, and monitoring. The results of the activity indicate that the distribution of KHBS went well through coordination between the local government, sub-district government, village government, volunteers, and the beneficiary community. The community gave a positive response because the program was considered to help meet basic needs and support the economic conditions of families, although there were still obstacles related to access to disbursement of assistance and the accuracy of targeting beneficiaries.